2021
DOI: 10.1101/2021.04.19.440384
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bone innervation and vascularization regulated by osteoclasts contribute to refractive pain-related behavior in the collagen antibody-induced arthritis model

Abstract: Objective: Rheumatoid arthritis is often characterized by eroded joints and chronic pain that outlasts disease activity. Whilst several reports show strong associations between bone resorption and nociception, the underlying mechanisms remain to be unraveled. Here, we used the collagen antibody-induced arthritis (CAIA) model to examine the contribution of osteoclasts in pain regulation. The antinociceptive effects of osteoclasts inhibitors and their mechanisms of actions involving bone vascularization and inne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Netrin-1 is an axon guidance molecule known to play a pivotal role in neurogenesis through binding to its canonical receptors UNC5 homolog (UNC5H) and deleted in colorectal cancer (DCC) (Madison et al, 2000; Dun and Parkinson, 2017; Boyer and Gupton, 2018). Previous studies have demonstrated a role of netrin-1 on sensory nerve sprouting (Zhu et al, 2019); moreover, silencing netrin-1 reduces hyperalgesia and CGRP+ nerve fiber sprouting in a rat model of disc degeneration (Zheng et al, 2023) and pharmacological netrin-1 inhibition with the NP-137 anti-netrin-1 antibody reduced hyperalgesia in an arthritis model (Rudjito et al, 2021). To investigate whether blockade of periosteal nerve sprouting attenuated MIBP, 5TGM1-GFP inoculated mice were systemically treated with vehicle (MM VEH ) or NP137 (MM NP137 ; 10 mg/kg, i.p).…”
Section: Resultsmentioning
confidence: 99%
“…Netrin-1 is an axon guidance molecule known to play a pivotal role in neurogenesis through binding to its canonical receptors UNC5 homolog (UNC5H) and deleted in colorectal cancer (DCC) (Madison et al, 2000; Dun and Parkinson, 2017; Boyer and Gupton, 2018). Previous studies have demonstrated a role of netrin-1 on sensory nerve sprouting (Zhu et al, 2019); moreover, silencing netrin-1 reduces hyperalgesia and CGRP+ nerve fiber sprouting in a rat model of disc degeneration (Zheng et al, 2023) and pharmacological netrin-1 inhibition with the NP-137 anti-netrin-1 antibody reduced hyperalgesia in an arthritis model (Rudjito et al, 2021). To investigate whether blockade of periosteal nerve sprouting attenuated MIBP, 5TGM1-GFP inoculated mice were systemically treated with vehicle (MM VEH ) or NP137 (MM NP137 ; 10 mg/kg, i.p).…”
Section: Resultsmentioning
confidence: 99%